Right ventricular outflow tract tachycardia after an initial dose of amantadine - Cüneyt Kocaş; Yusuf Türkmen; Gökhan Çetinkal; Sait Mesut Doğan (KARE Publishing, 2015)
Amantadine hydrochloride is an antiviral agent that is also effective in the treatment of Parkinson's disease. In the literature, cardiac arrhythmia is reported in toxic doses of amantadine, but in this paper we report a patient with right ventricular outflow tract (RVOT) tachycardia after an initial dose of amantadine. A 47-year-old female patient was admitted to the emergency department with the complaint of palpitation and dizziness after taking 200 mg amantadine. A 12-lead standard ECG showed wide QRS complex tachycardia with a heart rate of 167/min. The wide QRS complex tachycardia had an inferior axis and left bundle branch block morphology, compatible with RVOT ventricular tachycardia (RVOT-VT). Tachycardia terminated spontaneously and sinus ECG was completely normal. No arrhythmia was inducible at the electrophysiological study. To the best of our knowledge, this is the first case in the literature to describe RVOT-VT after amantadine intake. Amantadine may cause RVOT-VT as well as other cardiac arrhythmias.